A morte da pessoa humana entre o critério de morte encefálica e o do fim da circulação sanguínea: debate bioético a partir da nova teoria da lei natural - CABEÇA, Ana Carolina Costa (2022)
This study deals with the problem of the dignity of people due to organ procurement for transplantation after whole-brain death based on a philosophical discussion among different authors of the theory of natural law based on the studies of Thomas Aquinas. There are authors like Craig Payne and D. Alan Shewmon who condemn the procedure, stating that it dehumanizes the brain-dead donor, injuring his dignity and taking his life; these authors consider that the most adequate criterion for determining the death of a human being is the absence of blood circulation in the patient's body. On the other hand, Jason T. Eberl, Patrick Lee and Germain Grisez defend organ collecting in these cases, claiming that after whole brain death, the body is no longer a component of a human person, thus, there is a substantial change in the being. The article concludes that the position of J. T. Eberl, P. Lee and G. Grisez is the one that best fits the Thomistic concept of death - the end of the existence of a human being. Therefore, the collecting of organs for transplantation after whole-brain death does not violate human dignity or the donor's right of life.